(untitled) (Al-Academy, 2025)
Photography is one of the most important pillars of a dramatic achievement, as the director relies on the photography process to convey an idea to the mind of the viewer. One of the most prominent problems that the photographer suffers from in outdoor photography is the climate and terrain and their factors that negatively affect the efficiency of the outdoor photography process. The research problem can be summed up by asking: The following: What are the problems that affect external filming of television work in the Iraqi environment? The importance of the research comes from highlighting the problems and obstacles facing the photographer during the outdoor photography process in the climatic environment.The theoretical framework covered two sections, the first being interactive integration, and the second section: designing magazine covers, with indicators for this theoretical framework, the art of photography and its origins, television photography, outdoor photography and its types. The emergence and development of Iraqi television drama. The research procedures included the research community, research samples, and its tool. We followed by analyzing a selected film and concluded the research with results and conclusions, including:1. Weak production capabilities and poor quality of outdoor photography equipment led to the inability to overcome unnatural environmental factors, such as outdoor photography locations in rugged and unstable areas.2. Inaccurate choices of filming locations contributed to obstructing outdoor filming, as well as causing poor execution of the scenes visually and audio, as well as the rest of the other montage elements.